Effect of Co2+ substitution in B-sites of the perovskite system on the phase formation, microstructure, electrical and magnetic properties of Bi0.5(Na0.68K0.22Li0.10)0.5TiO3 ceramics - Bhupaijit, Pamornnarumol; Kaewsai, Chonnarong; Suriwong, Tawat; Pinitsoontorn, Supree; Yotthuan, Surirat; Vittayakorn, Naratip; Bongkarn, Theerachai (My University, 2022)
Bi0.5(Na0.68K0.22Li0.10)0.5Ti1−xCoxO3 lead-free perovskite ceramics (BNKLT−xCo, x = 0, 0.005, 0.010, 0.015 and 0.020) were fabricated via the solid-state combustion technique. A small-amount of Co2+ ion substitution into Ti-sites led to modification of the phase formation, microstructure, electrical and magnetic properties of BNKLT ceramics. Coexisting rhombohedral and tetragonal phases were observed in all samples using the X-ray diffraction (XRD) technique. The Rietveld refinement revealed that the rhombohedral phase increased from 39% to 88% when x increased from 0 to 0.020. The average grain size increased when x increased. With increasing x, more oxygen vacancies were generated, leading to asymmetry in the bipolar strain (S−E) hysteresis loops. For the composition of x = 0.010, a high dielectric constant (εm) of 5384 and a large strain (Smax) of 0.23% with the normalized strain (d*33) of 460 pm·V−1 were achieved. The BNKLT−0Co ceramic showed diamagnetic behavior but all of the BNKLT−xCo ceramics exhibited paramagnetic behavior, measured at 50 K.
Keywords: BNKLT−xCo; dielectric; ferroelectric; magnetic; strain